Dephosphorylation of cofilin is regulated through Ras and requires the combined activities of the Ras-effectors MEK and PI3K - Nebl, Gabriele; Fischer, Sabine; Penzel, Roland; Samstag, Yvonne (Cellular signalling, 2004)
Remodeling of the actin cytoskeleton is crucial for a multitude of cellular functions including cell movement, intracellular transport as well as signal transduction and gene expression processes. Cofilin has been identified as a key mediator of actin reorganization. Its activity is regulated via reversible phosphorylation of ser-3. In a variety of cell types stimulation through particular surface receptors fastly induces the dephosphorylation/activation of cofilin. Yet, the signal transduction cascades linking receptor stimulation with cofilin activation have not been identified so far. Here we show that the GTPase Ras acts as a central regulator of the cofilin dephosphorylation pathway. Thus, stimulation of Ras through platelet-derived growth factor (PDGF) or transient expression of activated Ras-proteins induces the dephosphorylation of cofilin. Importantly, the cooperation of two Ras-initiated signaling pathways is required to induce cofilin dephosphorylation: a Ras-Raf-MAPkinase/Erk-kinase (MEK)- and a Ras-phosphatidylinositol-3-kinase (PI3K)-effector cascade.